Synergistic insecticidal efficacy of Beauveria bassiana with silver nanoparticles against Bihar hairy caterpillar, Spilarctia obliqua (Walker) infesting Green gram (Vigna radiata) - MAHESHWARI, SOURABH (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted to evaluate insecticidal efficacy of entomopathogenic fungus, Beauveria bassiana alone and in combination with biosynthesized silver nanoparticles (AgNPs) against Bihar hairy caterpillar, Spilarctia obliqua (Walker) infesting green gram (Vigna radiata) under laboratory and net house conditions. The study showed that all the concentrations of AgNPs were compatible up to 10 ppm for the growth of B. basssiana and the combination of AgNPs (40 ppm) and B. bassiana (6.1 x 108) showed LC50 at 11.16 ppm and LT50 at 77.31 hours under laboratory condition. This combination was found 2.85 times more toxic than AgNPs alone. Under net house conditions, this combination brought cent percent probit mortality on 8th DAT. This novel approach for pest management showed significantly appreciable results for achieving synergistic insecticidal efficacy with the combination of microbial pesticide with nanoparticles.